2022
DOI: 10.1111/1471-0528.17248
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of p16/Ki67 dual‐stain cytology for detection of cervical intraepithelial neoplasia grade two or worse in women with a transformation zone type 3: A cross‐sectional study

Abstract: Objective To evaluate the clinical utility of p16/Ki67 dual‐stain (DS) compared with cytology for detecting cervical intraepithelial lesion grade two or worse (CIN2+) in women with a transformation zone type 3 (TZ3). Design Cross‐sectional study. Setting Colposcopy clinics in Central Denmark Region. Population Women aged 45 years or older referred for colposcopy because of an abnormal screening test. Methods All women had a cervical sample collected for cytology and DS testing and underwent large‐loop excision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Dear Dr. Papageorghiou, With interest, we read the letter to the editor entitled: 'Beyond P16/Ki67 dual-stain cytology: exploring alternative biomarkers for diagnosing cervical cancer and its precursors' by Shah Hussain and colleagues. 1 We thank the authors for their interest in our article.…”
Section: Author' Replymentioning
confidence: 91%
See 1 more Smart Citation
“…Dear Dr. Papageorghiou, With interest, we read the letter to the editor entitled: 'Beyond P16/Ki67 dual-stain cytology: exploring alternative biomarkers for diagnosing cervical cancer and its precursors' by Shah Hussain and colleagues. 1 We thank the authors for their interest in our article.…”
Section: Author' Replymentioning
confidence: 91%
“…Beyond P16/Ki67 dual-stain cytology: Exploring alternative biomarkers for diagnosing cervical cancer and its precursors Dear Dr. Papageorghiou, We read with interest the article 'Clinical utility of p16/Ki67 dual-stain cytology for detection of cervical intraepithelial neoplasia grade two or worse in women with a transformation zone type 3: a cross-sectional study' by Gustafson et al 1 We appreciate the authors' emphasis on the clinical utility of p16/Ki67 dual-stain cytology and would like to offer some addition war insights.…”
Section: E T T E R S T O T H E E D I T O Rmentioning
confidence: 99%
“…In our article 'Clinical utility of p16/Ki67 dual-stain cytology for detection of cervical intraepithelial neoplasia grade two or worse in women with a transformation zone type 3: a cross-sectional study', 2 we found that, compared with cytology, the p16/Ki67 dual stain had superior sensitivity and negative predictive value for detecting cervical intraepithelial neoplasia grade two or worse (CIN2+) in women with a transformation zone type 3 (TZ3) at colposcopy. We demonstrated that p16/Ki67 dual stain could be a valuable risk marker to guide clinical management in a group of women with abnormal screening results where colposcopy is very challenging.…”
Section: Author' Replymentioning
confidence: 95%
“…Line Winther Gustafson 1,2 Mette Tranberg 1 Pia Nørgaard Christensen 3 Rikke Brøndum 3 Nicolas Wentzensen 4 Megan A. Clarke 4 Berit Andersen 1,5 Lone Kjeld Petersen 6,7 Pinar Bor 5,8 Anne Hammer 5,9…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N T Not Applicablementioning
confidence: 99%

Authors' reply

Gustafson,
Tranberg,
Christensen
et al. 2023
BJOG
Self Cite
“…Clinical guidelines for use of dual stain in cervical cancer screening programs are currently in development. Several studies have demonstrated that p16 and p16/Ki-67 dual stain cytology have shown greater accuracy for the detection of cervical precancers compared with cervical cytology, [140][141][142][143][144][145][146] with evidence suggesting that a negative dual stain result provides longer reassurance against the risk of cervical precancer than negative cytology. 147 It has been demonstrated that the dual stain assay can be implemented with little training and that it is highly reproducible; 145,148,149 however, like cytology, dual stain testing requires specialized infrastructure and expertise for the interpretation of stained slides.…”
Section: Hpv Genotypingmentioning
confidence: 99%